2008
DOI: 10.1007/s11064-008-9775-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Stress Response: A Novel Target for Chemoprevention and Nutritional Neuroprotection in Aging, Neurodegenerative Disorders and Longevity

Abstract: The predominant molecular symptom of aging is the accumulation of altered gene products. Moreover, several conditions including protein, lipid or glucose oxidation disrupt redox homeostasis and lead to accumulation of unfolded or misfolded proteins in the aging brain. Alzheimer's and Parkinson's diseases or Friedreich ataxia are neurological diseases sharing, as a common denominator, production of abnormal proteins, mitochondrial dysfunction and oxidative stress, which contribute to the pathogenesis of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
230
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(233 citation statements)
references
References 323 publications
(392 reference statements)
2
230
0
1
Order By: Relevance
“…After a CNS injury, Hsp70 is synthesized at high levels and is present in the cytosol, nucleus, and endoplasmic reticulum [52]. Hsp60 chaperone proteins within mitochondria and, also, protect brain cells against ischemia and seizures in vivo, after viral-induced overexpression [18]. Hsp60 is encoded in the nucleus and resides mainly in the mitochondria [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After a CNS injury, Hsp70 is synthesized at high levels and is present in the cytosol, nucleus, and endoplasmic reticulum [52]. Hsp60 chaperone proteins within mitochondria and, also, protect brain cells against ischemia and seizures in vivo, after viral-induced overexpression [18]. Hsp60 is encoded in the nucleus and resides mainly in the mitochondria [53].…”
Section: Discussionmentioning
confidence: 99%
“…To date this is the first report demonstrating changes in thioredoxin/thioredoxin reductase protein levels in MS patients. Thioredoxin (TRX) represents an intracellular redox regulator that has been shown to be important for the regulation of redox-sensitive transcription factors [18]. In its reduced state TRX can oxidatively reactivate inactive transcription factors such as Jun, Fos, AP-1, redox factor-1 (ref-1), and Nrf-2 [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, experimental rodent models of myocardial infarction and stroke on an intermittent fasting (IF) regimen exhibit increased resistance of heart and brain cells to ischemic injury. The beneficial effects of IF and caloric restriction (CR) result from at least two mechanisms, namely reduced oxidative damage and increased cellular stress resistance (Calabrese et al, 2008). In the epidemiology of neurodegenerative diseases, the incidence of sporadic Parkinson's disease (PD) and suggested that restriction of calorie intake is crucial for the prevention of learning and memory deficits in different animal models (Komatsu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%